COMPARISON OF NASOLABIAL ANGLE IN YOUNG ADULTS AND MIDDLE AGED DENTATE AND ELDERLY EDENTULOUS SUBJECTS: Nasolabial Angle - A Comparative Study - Azad, Lt Col Azad Ali; Akhtar, Qayyum; Ibrahim, Shazia Zareen Aqeel; Aziz, Faisal; Hasan, Syed Hammad (Pakistan Armed Forces Medical Journal, 2010)
Objective: To compare the mean value of nasolabial angle in dentate and edentulous subjects in young adults, middle aged dentate (having normal occlusion) and elderly edentulous subjects.Study Design: Cross-sectional comparative studyPlace and Duration of Study: The study was conducted in the Department of Prosthodontics, Armed Forces Institute of Dentistry, and Army Medical College, Rawalpindi from September 2007 to November 2008.Patients and Methods: A total of 250 subjects were divided in three age groups. Group 1: 100 Subjects 20–30 years , Group 2: 100 subjects 35-45 years and Group 3: 50 edentulous subjects >50 years. The subjects with Intact maxillary and mandibular arches and Angle’s Class-I molars, canine and incisor relationship were included. Standard lateral cephalometric radiographs of the heads were traced and nasolabial angle was measured.Results: The mean values of nasolabial angle in dentate and edentulous were 96.79°±2.6 and 111.40o±2.51respectively. The mean values of nasolabial angle in young adults (20-30 years), middle aged (35-45 years) and old edentulous (>50 years) subjects were 97.39o±2.94, 96.19o±2.58 and 111.40o±2.51respectively. The difference in mean values of nasolabial angle among three groups, was statistically significant (p